The Famous Poisonings in History - Arturo J. Brugger Aubán (Swiss Journal of Radiology and Nuclear Medicine)
The use of poisons spans human history, serving as tools for war, execution, assassination, revenge, and political control. Ancient texts like the "Rig Veda" mention poisoned weapons, and many civilizations used natural toxins—such as frog skin, snake venom, and plant extracts—for lethal purposes. Mythology reflects deep knowledge of poisons. Medea attempted to poison Theseus with aconite to protect her son’s claim to the throne. Hercules used Hydra’s venom to create deadly arrows. In historical contexts, figures like Socrates were executed with poison—hemlock in his case—which was reserved for elite criminals due to its cost. Classical toxicology began in Ancient Greece and continued through the Roman Empire. During Rome’s imperial era, poisons were commonly used in power struggles. Tiberius’ reign saw suspected poisonings of his potential successors, including Germanicus and Drusus. Caligula ultimately rose to power through such intrigue, killing his rivals. Notable toxicologists include Mateo Orfila, who advanced forensic detection techniques in the 19th century, and Juan Bautista Peset Aleixandre, who developed early devices to detect toxic gases in the blood. Natural poisons were also studied in modern science. Cobra venom contains dozens of toxic proteins, many of which disrupt nerve and muscle function. Aconitine, found in "Aconitum napellus", binds to sodium channels in nerves, keeping them open and causing fatal disruptions in cell signaling. Another plant-based toxin, protoanemonin from buttercups, causes painful spasms and ulcers, giving rise to the term "sardonic smile". In Renaissance and Baroque Europe, poisoners like Locusta in Nero’s Rome and La Voisin in Louis XV’s court gained notoriety for their lethal skills. They supplied aristocrats with toxic mixtures to remove rivals or secure inheritances. One infamous potion, “Aqua Tofana”, was linked to hundreds of deaths, possibly including that of Mozart. Venice’s secretive Council of Ten used poison for state security, relying on anonymous citizen reports and aconite-based poisons. In France, women like the Marquise de Brinvilliers and La Voisin were executed for mass poisonings. These individuals often disguised their poisons as medicine or spiritual remedies, exploiting trust and social status. Through myth, science, and scandal, poisons have left an indelible mark on human history, both as instruments of death and as subjects of fascination and fear.